Edukasi Literasi Keuangan Bagi Anggota Karang Taruna di Komplek Griya Caraka Bandung - Hernawati, Euis; Candra Fatihah, Dian; Warsiati, Wiwi; Dewi Pramanik, Nuniek; Nurdin, Jusuf (PADMA, 2024)
This training aims to provide knowledge and insight to members of the youth organization in RW 05 Griya Caraka Complex, Cisaranten Endah Village, Arcamanik District, Bandung. The members of the youth organization are given provisions on how to manage finances and develop available funds so that they can increase and be utilized properly. The activity methods used are lecture and practice methods. The results of the activity show that members of the youth organization have a better understanding and knowledge of financial institutions and financial products and services, including features, benefits and risks related to financial products and services.